2020
DOI: 10.3928/01913913-20200417-01
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Tumor Recurrence Following Primary Intravenous Chemotherapy (Chemoreduction) for Retinoblastoma in 869 Eyes of 551 Patients

Abstract: Purpose: To identify risk factors for retinoblastoma recurrence following chemoreduction. Methods: This was a retrospective review of patients with retinoblastoma treated from 1994 to 2019 using chemoreduction with analysis for recurrence using Kaplan–Meier, Cox regression, and logistic regression. Results: There were 869 eyes of 551 patients with retinoblastoma treated with chemoreduction. Fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 23 publications
2
18
0
Order By: Relevance
“…ICRB grouping predicted success of eye‐preserving systemic chemotherapy in multiple other study cohorts 17,18,34 . This finding is in line with a significantly lower EFES and OES for advanced intraocular tumors (ICRB D/E eyes) compared with ICRB A/B/C eyes after both chemotherapy regimens in our study.…”
Section: Discussionsupporting
confidence: 87%
See 4 more Smart Citations
“…ICRB grouping predicted success of eye‐preserving systemic chemotherapy in multiple other study cohorts 17,18,34 . This finding is in line with a significantly lower EFES and OES for advanced intraocular tumors (ICRB D/E eyes) compared with ICRB A/B/C eyes after both chemotherapy regimens in our study.…”
Section: Discussionsupporting
confidence: 87%
“…ICRB grouping predicted success of eye-preserving systemic chemotherapy in multiple other study cohorts. 17,18,34 Until end of the study, no SPM has been reported in any of the two groups, but longer follow-up is required to validate this hypothesis because second cancers may occur decades after treatment for retinoblastoma. 35,36 Transient hematological toxicity, especially severe neutropenia, was a common side effect that occurred after about three-fourths of all chemotherapy cycles.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations